Measurement properties of self-reported outcome measures for older adults with nonspecific low back pain: a systematic review - Huang, Frank F; Liang, Jitong; Lin, Chung-Ying; Samartzis, Dino; Karppinen, Jaro; Zheng, Yongping; Zhou, Zhixing; Zheng, Daniel K Y; Chang, Jeremy R; de Luca, Katie; Wong, Arnold Y L (Age and ageing, 2025)
To summarise the measurement properties of patient-reported outcome measures (PROMs) for older adults with nonspecific low back pain. Eight databases were searched from inception to January 2024. Two independent reviewers conducted article screening, data extraction, risk of bias assessments, evaluations of measurement properties of PROMs, syntheses of quality of evidence and forming recommendation levels using relevant checklists and assessment tools. Ten PROMs were identified from 12 included studies. The Functional Rating Index, Oswestry Disability Index, Roland Morris Disability Questionnaire and Quebec Back Pain Disability Scale demonstrated the highest recommendation (category A: PROM most suitable) for evaluating pain-related functional limitation or pain intensity in older adults with acute, subacute or chronic nonspecific low back pain. The Pain Response to Activity and Positioning questionnaire obtained a category A recommendation for making a differential diagnosis of chronic nonspecific low back pain in older adults. The 36-Item World Health Organization Disability Assessment Schedule 2.0 was considered promising (category B: PROM recommended) for assessing physical functioning, while the Back Believe Questionnaire, Catastrophizing Avoidance Scale D-65+, Pain Catastrophizing Scale and Psychological Inflexibility in Pain Scale obtained category B recommendation for evaluating negative thoughts in this population, although further validation is warranted. This systematic review identified suitable PROMs for assessing physical function in older adults with nonspecific low back pain, but more studies are needed to evaluate the measurement properties of questionnaires on other outcome domains in this population.